Entrepreneurs’ strategic response to COVID-19 limitations: Ukrainian experience - Yeliena Prokhorova; Mykhailo Sahaidak; Tetiana Sobolieva (Anali Ekonomskog fakulteta u Subotici, 2022)
COVID-19 quarantine limitations and their effects on business lead to unpredictable environment changes, which require appropriate entrepreneurs’ strategic response. COVID-19 quarantine limitations dramatically affected specialized businesses, which had to adopt for the new environment requirements. COVID-19 especially influenced small and medium size entrepreneurs, which are specialized in one industry. Considering the peculiarities of integration and diversification as priority strategies for business development in the new reality, the article proves that specialization in goods or services in one industry for small and medium enterprises is risky and can lead to the bankruptcy of such businesses. Based on official statistics, the changes in Ukrainian small and medium companies’ performance during years 2019-2020 were studied across industries. The gathered data provide evidence that companies which specialized in one industry or business activity suffered from the crisis most of all. According to the forecasts, COVID-19 will affect the economy over a number of years. That is why business has to adopt for the new reality. Using diversification strategies for small and medium size businesses is recommended in order to survive and grow.